Causes of Increased Competition in the U.S. Economy, 1939-1980 - Shepherd, William G. (The Review of Economics and Statistics, 1982)
Examines the sources of increased competition in the United States (U.S.) between 1939 to 1980. In this paper authors consider the review of related literature, trends and patterns of competitive structure in the U.S. economy, influence of antirust actions on competition.